Innovation of Healthy and Halal Menu in The Maqosid Shari'ah Perspective School Canteen in Tanjung Jabung Timur - A. Syamsi; Muhammad Mashduqi; Zaenal Abidin; Daud (Swakarya: Jurnal Penelitian Sosial dan Pengabdian Masyarakat, 2024)
The innovation of healthy and halal menus in school canteens in East Tanjung Jabung aims to improve the quality of nutrition and compliance with the principles of maqasid sharia in student food consumption. This research highlights the importance of providing food that not only meets healthy and halal criteria, but also nutritious, to support the health and development of students. By implementing the concept of BERHAZI (Diverse, Halal, Nutritious) canteens, schools can provide more varied and attractive food options for students. Collaboration with halal-certified local producers is the main strategy to ensure the supply of quality foodstuffs. In addition, regular audits of the serving process and cleanliness in school canteens are needed to maintain halal standards and food safety. Nutrition education for students, teachers, and canteen managers is also the main focus to increase awareness of the importance of healthy eating. The involvement of parents and communities in healthy school programs can strengthen the implementation of these initiatives. Through a holistic approach that involves various parties, it is hoped that this innovation can create an educational environment that supports student health and integrates halal values in food consumption. This research provides insight into how innovative programs in school canteens can serve as a catalyst in creating a younger generation that is healthier and more responsive to religious values in daily life. In addition, the results of this research are expected to be a reference for education and health policies in other regions, as well as encourage further development regarding the provision of healthy and halal food in educational institutions. This shows that the integration of education, auditing, and collaboration activities has succeeded in improving the performance of school canteens in providing balanced and safe food for consumption.